Faktor-faktor yang Mempengaruhi Keputusan Petani Mangga dalam Pemilihan Pasar di Kabupaten Indramayu - Rani Andriani; Elly Rasmikayati; Gema Wibawa Mukti; Sri Fatimah (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2019)
Increasing domestic demand for mangoes in recent years has increased rapidly, not only in terms of quantity but also in terms of quality of mango, especially for modern markets. But only a small part of the mango which could entered the modern market. Understanding of farmers' access to markets is needed to increase farmers' capacity as an effort to improve farmers' welfare. The purpose of this research were to: 1) Analyze socioeconomic characteristics of mango farmers in Indramayu Regency; 2) Analyze the mango marketing channelin Indramayu District; 3) Analyze the factors that influence the decision of mango farmers in market selection in Indramayu District. This research is a quantitative research with 130 mango farmers who were taken by using multi stage random sampling. Data were analyzed descriptively as well as logistic regression analysis. The results showed that most of the farmers were in productive age, had completed primary school education, had <100 trees, never participated in the activity, did not join to farmers group and partnership in marketing. Most farmers market their crops to collecting traders. The level of education of farmers, frequency of extension activities, access to information about mango’s market, quality requirements, the percentage of mango of goodquality and the attachment of farmers to certain financing sources are the factors that significantly influence the farmer's decision in choosing the market. The role of farmer groups is needed to collect farmers in marketing their crops with profitable systems for farmers.